ATTITUDES TOWARDS MORAL HERITAGE IN THE HISTORY OF CENTRAL ASIA (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article examines how the attitudes of Central Asian peoples towards the socio-philosophical and moral heritage have been evaluated from a historical perspective. It also provides a philosophical analysis that an objective attitude towards the moral heritage of the past, as well as such an attitude towards the moral heritage of the peoples of the world, can have a positive impact on raising the moral qualities of our people to a higher level.